Psychology according to the pluralized epistemology - Kinouchi, Renato Rodrigues (Perspectivas em Análise do Comportamento, 2023)
This work comments on the relationships between epistemology and the history of psychology discussed by José Antônio Damásio Abib. First, it shows that the adoption of a unitary view of epistemology leads the historian of psychology to an aporia, because, due to the lack of unity in the psychological field, it would not be possible to make the history of such a science that has not been unified yet. On the other hand, the adoption of a pluralist view of epistemology leads to a history of psychological culture capable of accommodating and making sense of the fact that Wundt’s and James’ scientific psychology projects had very significant differences. Finally, it is emphasized that unified epistemology has another unwanted effect, namely, that of impoverishing the debate by preventing different interpretations from being mobilized in the research.